Efficacy of Electroacupuncture Therapy in Patients With Postherpetic Neuralgia: Study Protocol for a Multicentre, Randomized, Controlled, Assessor-Blinded Trial - Hu, Hantong; Shen, Yejing; Li, Xinwei; Tian, Hongfang; Li, XingLing; Li, Yang; Cheng, Yingying; Wu, Lei; Han, Dexiong (Frontiers in Medicine, 2021)
Introduction: The efficacy of conventional treatments for treating postherpetic neuralgia (PHN) remains unsatisfactory. Thus, this multicentre, randomized controlled, assessor-blinded trial aims to investigate the efficacy and safety of electroacupuncture (EA) therapy in patients with PHN. Methods and Analysis: This multicentre randomized controlled trial will enroll 132 patients with PHN from 3 hospitals. All patients will be randomly assigned to either the EA combined with medication group or medication group through a computerized central randomization system in a 1:1 ratio. Outcome measures will be assessed before intervention, at 2, 4, 6 weeks after intervention and at the end of 8-week follow-up. Primary outcomes will be sensory thresholds and pain intensity. Secondary outcomes will include dosage of analgetic, quality of life, anxiety, and depression severity and sleep quality. All adverse effects will be assessed during the trial. Conclusions: This study will provide evidence to ascertain whether EA is effective and safe for treating PHN. Ethics and Dissemination: Ethics approval (No.ZSLL-KY-2017-025) has been obtained from the Ethics Committee of The Third Affiliated Hospital of Zhejiang Chinese Medical University. Informed consent will be signed prior to subject enrolment. The results will be submitted to international peer-reviewed journals and presented at international conferences. Trial Registration Number: The study protocol has been registered in the clinicaltrials registry with the identification code NCT04594226.